A critical comparative evaluation on DHT-based peer-to-peer search algorithms. (1st January 2014) - Betts, Alexander; Liu, Lu; Li, Zhiyuan; Antonopoulos, Nick
Peer-to-peer networks are becoming increasingly popular as a method of creating highly scalable and robust distributed systems. To address performance issues when scaling traditional unstructured protocols to large network sizes many protocols have been proposed which make use of distributed hash tables to provide a decentralised and robust routing table. This paper investigates the most significant structured distributed hash table (DHT) protocols through a comparative literature review and critical analysis of results from controlled simulations. This paper discovers several key design differences, resulting in pastry performing best in every test. Chord performs worst, mostly attributed to its unidirectional distance metric, while significant generation of maintenance messages hold Kademila back in bandwidth tests.